Knowledge Mobilization Practices of Educational Researchers Across Canada - Cooper, Amanda; Rodway, Joelle; Read, Robyn (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
Researchers are under increasing pressure to disseminate research more widely with non-academic audiences (efforts we call knowledge mobilization, KMb) and to articulate the value of their research beyond academia to broader society. This study surveyed SSHRC-funded education researchers to explore how universities are supporting researchers with these new demands. Overall, the study found that there are few supports available to researchers to assist them in KMb efforts. Even where supports do exist, they are not heavily accessed by researchers. Researchers spend less than 10% of their time on non-academic outreach. Researchers who do the highest levels of academic publishing also report the highest levels of non-academic dissemination. These findings suggest many opportunities to make improvements at individual and institutional levels. We recommend (a) leveraging intermediaries to improve KMb, (b) creating institutionally embedded KMb capacity, and (c) having funders take a leadership role in training and capacity-building.